SHARE PRICE REACTION TO BLACK MANAGEMENT APPOINTMENTS IN SOUTH AFRICA - Lowe, Craig (My University, 2011)
Research conducted both locally and internationally has yielded mixed results to changes in top management. However, once management changes are classified according to the post of an executive and according to the circumstances surrounding the changes, a statistically significant share price reaction is usually observed. This study utilises standard event methodology to determine the share price reaction to black executive management appointments for companies listed on the Johannesburg Stock Exchange. A statistically significant cumulative abnormal return of 3.39% was found to exist over the two day announcement period. The sample comprises all black executive management appointments publicly announced in appointment-only announcements between 1st July 2000 and 30th June 2005. The findings are relevant in South Africa where the market is experiencing the overarching phenomenon of Black Economic Empowerment. Possible causes of the positive share price reaction are suggested
MBA - WBS
Keywords: Share price movements; Black economic empowerment; Johannesburg Securities Exchange